Pelaksanaan Asesmen Diagnostik: Tes Kepribadian Siswa Kelas VII di SMPN 4 Keruak - Indrawati; Samsul Bahri; Muh. Rusmayadi; Muh. Galang Isnawan; Imam Pakhrurrozi (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
SMPN 4 Keruak is one of the driving schools, with one of its programs namely learning with a new paradigm. To support the program, the community service team (PkM) conducted a diagnostic assessment. This is done with the aim of being the teacher's consideration in determining the appropriate teaching materials and learning methods to be used so that the information provided to students can be maximized. The diagnostic assessment carried out by the PkM team is a non-cognitive diagnostic assessment that focuses on knowing the type of personality possessed by class VII students of SMPN 4 Keruak. Student personality diagnostics is carried out using the AKU PINTAR application and web which is available on Android, students only need to fill out the test using a smartphone or laptop. The results obtained are that the dominant personality in class VII students of SMPN 4 Keruak is a combination of three personalities, namely dominance, influence, and steadiness. This means that students have a strong leadership spirit, tend to be nimble in acting and oriented to the future. By knowing the type of student personality, the teacher can arrange teaching materials and choose the right learning method to be used at the time of learning later.